(untitled) (Journal of the College of Basic Education, 2022)
There are several reports about using Teucrium polium (TP) in traditional medicine mainly for its antipyretic, antibacterial, antiinflammatory, antioxidant, antialcerogenic, antispasmodic, anti diabetic, hepatotoxicity and for fertility. Male mice was orally administrated by two concentration (50 mg/kg, 100 mg/kg) of TP aqueous extract to study the effect of this aqueous extract for period of time on fertility (live sperm, motility and abnormality). The result showed that there is significant difference (P<0.05) (in live sperm and motile sperm) between group treated with 100 mg/kg with control, while there was a significant difference in abnormality between the treated groups with the control. The increase in testes weight also indicate the positive effect referring to some TP constituents in the treated groups. The investigation has shown that the extract possesses promising fertility property which can be exploited in fertility therapy.